Process enhancements and wear evaluation of directed energy deposited bronze: Implications for reducing bronze in worm gear manufacturing - Sunil Raghavendra; Sasan Amirabdollahian; Matteo Perini; Priyadarshini Jayashree; Simone Perissinotto; Jan Coenen; Matteo Benedetti (Journal of Materials Research and Technology)
This study examines the application of Laser Directed Energy Deposition (L-DED) to reduce the use of bronze in the manufacturing of worm gears. Addressing the gap in research regarding the L-DED of bronze on steel substrates, the study refines process parameters to improve deposition quality significantly. The approach involves depositing single bronze tracks using various combinations of process parameters, followed by the analysis of cross-sections to evaluate porosity and track cross-section geometry. Building on the optimized parameters identified during single-track experiments, we achieve multi-layer depositions of 3 mm thickness. These layers are then transformed into cylindrical specimens that are subjected to rigorous wear testing in a pin-on-disc setup against a 42CrMo4V counterpart under dry sliding conditions, aimed at investigating debonding and friction characteristics. Additionally, disc-shaped specimens created with the optimized parameters are evaluated under lubricated conditions via a disc-on-disc test, accurately replicating motor gear loading scenarios. Comprehensive assessments of porosity, microstructure, and microhardness are conducted on these specimens. Finally, our findings reveal the potential of DED bronze as a groundbreaking alternative to traditional wrought bronze in gear applications, highlighting its promise for reducing bronze usage in worm gears with an enhanced wear performance.